Nutritional status of children registered in the SISVAN and analysis of public policies for tackling childhood obesity in the municipality of Rio Verde, Goiás (International Seven Journal of Health Research, 2023)
Obesity is a relevant topic, especially in children, as it is the period in which eating habits are formed, and it is possible to take preventive measures to prevent the spread of this disease and its consequences. Based on these arguments, the objective of the study was to point out the nutritional status of children aged 1 to 5 years old registered in SISVAN from 2018 to 2022 in the municipality of Rio Verde and Goiás and to describe public policies to combat obesity in the municipality of Rio Verde, Goiás . This research was cross-sectional, based on the SISVAN database. The sample covered all children under 10 years of age registered in the system in the municipality of Rio Verde-GO, from 2018 to 2022. The data show that in these years 6% of children aged 1 to 5 years in the municipality of Rio Green-go presented weight above age. Data considered high, due to the statistical sample and referring to the age group, a time when there should be many more healthy individuals.